Argentina : Economic Developments; January 25, 2013. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Argentina's economic developments and policies in the past 10 years. Argentina was recovering rapidly from the deep economic crisis of 2002, and the authorities had adopted policies conducive to a rapid decline in unemployment and poverty, a gradual recovery of the banking system, and a strengthening of the external position. The global environment foreseen at the time of the 2006 Article IV consultation with Argentina did not anticipate two major events that, in hindsight, turned out to be critical for the performance of the global economy, and Argentina, in the following years: global financial crisis of late 2008 and the sharp and persistent increase in world commodity prices.